Pengaruh Electronic Word Of Mouth, Harga Tiket Dan Lokasi Terhadap Keputusan Berkunjung Ke Objek Wisata Panyaweuyan - Qustolani, Asep; Hernita, Nita; Nurazizah, Elis (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
This study aims to determine the effect of Electronic Word of Mouth, Ticket Prices and Locations on Decisions to Visit Panyaweuyan Tourism Objects. The decision to visit is a major and important factor in the sustainability of a tourist attraction, but the decision to visit Panyaweuyan Tourism Object has decreased. The method used in this study is a survey method with a descriptive and verification approach. The population in this study is an infinite number of visitors to Panyaweuyan Tourism Object. The sample technique uses the Relative Allowable Error formula so that the number of samples is 100 visitors. The type of data used is primary data obtained from questionnaires distributed to all samples. Data analysis used descriptive analysis and verification analysis including classical assumption test, multiple linear regression analysis, coefficient of determination analysis and model feasibility test. Test the hypothesis using the t test. The results showed that partially Electronic Word of Mouth, Ticket Prices and Locations had a positive and significant effect on the Decision to Visit Panyaweuyan Tourism Objects. This means that the better the Electronic Word of Mouth, Ticket Prices and Locations, the higher the Visiting Decision.